SERVICE QUALITY AND BRAND IMAGE ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY AT PESONNA HOTEL PEKANBARU - Teddy Chandra; Rizaldi Putra; Jacksen (Journal of Applied Business and Technology, 2021)
The purpose of this study are (1) to determine, test and analyze the influence of Service Quality and Brand Image on Customer Satisfaction at Hotel Pesonna Pekanbaru (2) To determine, test and analyze the influence of Service Quality, Brand Image and Customer Satisfaction on Customer Loyalty at Hotel Pesonna Pekanbaru . In this study, the population is visitors of Hotel Pesonna Pekanbaru who have visited at least 2 times. The sample of this study was 120 respondents who were taken using purposive sampling with data collection methods using questionnaires. The analysis used is descriptive analysis and verification analysis. The data in this study were processed using SPSS, SmartPLS, and Microsoft Excel. The results of this study indicate that Service Quality (X1) has a significant effect on Customer Satisfaction (Y1). Service Quality (X1) has a significant effect on Customer Loyalty (Y2). Brand Image (X2) has a significant effect on Customer Satisfaction (Y1). Brand Image (X2) has a significant effect on Customer Loyalty (Y2). Customer Satisfaction (Y1) has no significant effect on Customer Loyalty (Y2).